Evaluating the Efficacy of a Behavior Modification Program In Overweight African American Adolescents... Revisiting the Literature. - Lane-Tillerson, Crystal (ABNF Journal)
Even though African-American and Caucasian American females have similar rates of overweight in infancy and childhood, overweight tends to increase in African-American females during adolescence. The disproportionate prevalence of overweight in African-American females and the critical period of adolescence indicate the need for research that focuses on exploring interventions to better meet the needs of African-American female adolescents. This article reports the most current statistics and literature related to overweight and obesity in comparison with this writer's dissertation research completed in 2005. It will outline the strides that have been made to counteract overweight and obesity in African-American adolescent girls and the outcomes of the interventions targeting this population over the past twelve years. A behavior modification program was conducted for the original dissertation study. The outcomes of this study will be compared to current interventions to determine lessons learned; indications for further research and proposed future interventions.